The Rhetorical Moves in the Students’ Introduction Parts of Theses Writing - Yustus Sentus Halum (Tell-us Journal)
This study aims to discover the rhetorical moves used by students in the English Language Education Study Program at UNIKA Santu Paulus Ruteng when writing the introductory part of their theses, using the Create A Research Space (CARS) Model. A qualitative method was employed to describe and interpret the data. The data source for this research consisted of the introductions of ten students’ theses, collected through stratified random sampling. A checklist was used as the main instrument for data collection. In analyzing the data, the researcher followed specific steps, such as identifying sentences and expressions that indicate each move, interpreting the data, and drawing conclusions based on the results. The findings revealed that the students used various rhetorical moves in their thesis introductions. Most students applied nearly all the moves, although one thesis did not include move 2 at all. Additionally, it was found that some steps in move 2, particularly steps 2a (counter-claiming) and 2b (indicating a gap), were often skipped by the students. Step 2b was never applied in any of the theses.